(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
Mental health has become a major issue in India’s higher education sector. Academic stress, socio-economic disparities, and more frequent student distress contribute to this problem. This paper looks at mental health policies within Indian higher education, viewing them through the lens of inclusivity. It explores their range, how they’re put into action, and their success among various student groups. The study relies on a qualitative review of secondary data like University Grants Commission policy documents, Supreme Court rulings in India, and statistics from the National Crime Records Bureau. The analysis shows that although there has been significant growth in policy frameworks, implementation varies widely between institutions. Problems such as insufficient resources still persist. Access to mental health services faces obstacles like lack of infrastructure, not enough trained counsellors, and differences across regions. Plus, many policies don’t focus enough on specific needs of marginalized groups. Students from poorer backgrounds, women, and minority communities often get overlooked. The paper suggests a need for targeted actions and better use of resources to connect policy goals with real-world practice. For mental health support in Indian higher education to be fair for everyone, the system must consider context and include all voices.